Cellular‐FLIP, Raji isoform (c‐FLIPR) modulates cell death induction upon T‐cell activation and infection. Issue 6 (2nd May 2013) - Telieps, Tanja; Ewald, Frida; Gereke, Marcus; Annemann, Michaela; Rauter, Yvonne; Schuster, Marc; Ueffing, Nana; von Smolinski, Dorthe; Gruber, Achim D.; Bruder, Dunja; Schmitz, Ingo
<x xml:space="preserve">Abstract</x> Dysregulation of apoptosis caused by an imbalance of pro‐ and anti‐apoptotic protein expression can lead to cancer, neurodegenerative, and autoimmune diseases. Cellular‐FLIP (c‐FLIP) proteins inhibit apoptosis directly at the death‐inducing signaling complex of death receptors, such as CD95, and have been linked to apoptosis regulation during immune responses. While the isoforms c‐FLIPL and c‐FLIPS are well characterized, the function of c‐FLIPR remains poorly understood. Here, we demonstrate the induction of endogenous murine c‐FLIPR in activated lymphocytes for the first time. To analyze c‐FLIPR function in vivo, we generated transgenic mice expressing murine c‐FLIPR specifically in hematopoietic cells. As expected, lymphocytes from c‐FLIPR transgenic mice were protected against CD95‐induced apoptosis in vitro. In the steady state, transgenic mice had normal cell numbers and unaltered frequencies of B cells and T‐cell subsets in lymphoid organs. However, when challenged with Listeria monocytogenes, c‐FLIPR transgenic mice showed less liver necrosis and better bacterial clearance compared with infected wild‐type mice. We conclude that c‐FLIPR expression in hematopoietic cells supports an efficient immune response against bacterial infections.